Effects of high fat diet and bamboo extract supplement on anxiety- and depression-like neurobehaviors in mice - Del Rosario, Adeline (Br J Nutr, 2012)
High fat diet is a major causative factor of overweight and obesity, which are associated with increased risk of neuropsychiatric diseases, such as anxiety and depression. In this study, we investigated the protective effects of bamboo extract (BEX) on anxiety- and depression-like neurobehaviors in mice treated with a high fat diet. Male mice with CD-1 genetic background were treated for 2 months with either a standard or a high fat diet (10% or 45% calories from fat, respectively), with or without BEX supplement (11 g dry mass per 17 MJ). The anxiety levels of the mice were evaluated using open field and hole-board tests, and depression was measured using force swimming test. The anxiety responses of the animals were found significantly increased after high fat diet treatment, and this elevation was effectively abolished by BEX supplement. High fat diet seemed to have an anti-depressive effect in the mice at the tested time point, but the effect of BEX supplement on the depression level of the animals was not conclusive. High fat diet significantly decreased total glutathione content in the blood while BEX supplement increased glutathione oxidation. In summary, this study showed that decreased total glutathione concentration in the blood co-occurred with high fat treatment, high anxiety level and low depression level in the mice; and when supplemented in a high fat diet, BEX had anxiolytic effect in the mice.